Empowering Employee Engagement: The Efficacy of Sports Activities as Stress Coping Mechanisms - Nadir Aliane; Ahmad Zakariya (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The significance of staff engagement in organisational performance lies in the enhanced efficiency and job satisfaction experienced by engaged individuals. Sports activities have been acknowledged as effective methods for enhancing employee involvement in the workplace. These endeavours not only enhance athletic motivation but also foster a sense of teamwork, leading to a more cohesive work environment. In addition, these programmes aid in promoting the physical well-being of employees by offering stress management techniques that have the potential to enhance overall health and performance. Hence, the objective of this research is to examine the impact of athletic activities on staff engagement, specifically focusing on sports motivation and engagement, team collaboration, and the physical fitness of employees as mechanisms for managing stress. The data has been gathered from the workforce in Saudi Arabia. The researcher employed an online survey methodology. The findings of the study indicate a significant and positive correlation between sports motivation and increased staff engagement. This correlation is accompanied by notable improvements in athletic motivation and team cooperation, which serve as effective strategies for enhancing job engagement. Nevertheless, the effectiveness of sports activities in promoting employee engagement is contingent upon factors such as the industry, organisational culture, and demographic composition. The limited consideration of contextual aspects in previous research has resulted in a constraint on the generalizability of findings to various organisations.